(untitled) (Canadian Perspectives on Academic Integrity, 2021)
While technology has made information readily available to university students, many of them have no sound understanding of how to use the sources properly, especially ESL students (Löfström & Kupila, 2013). When they use others’ ideas, text, or work without crediting the sources, they may commit either intentional or involuntary plagiarism (Camara et al, 2017). When they reuse a submitted assignment for another course improperly, they may commit self-plagiarism (APA Style, 2019), However, rather than simply punishing students for plagiarism, the universities should educate and empower students, especially ESL students, to avoid plagiarism (Khoo, 2021). Previous research has found student plagiarism to arise for such reasons as language incompetence, first culture influence, and time pressure (Camara et al., 2017; Löfström & Kupila, 2013; Shi, 2004, 2006). However, there might be other challenges ESL students encounter that are not well understood. To counter plagiarism, programs such as Turnitin have been developed to detect copying but it would be more ideal if teachers understand student needs and strategies to address them. Unfortunately, only limited research has studied these issues (Camara et al., 2017; Hu, 2001; Löfström & Kupila, 2013; Shi, 2006). Thus, this presentation reports on a study examining student perspectives on academic integrity challenges and institutional solutions. The study employed semi-structured individual in-depth qualitative interviews (Creswell, 2007; Hu, 2009) with 20 ESL students taking Academic Writing at a western Canadian university in Winter 2021. The participants were selected based on EDI (equity, diversity, and inclusiveness) principles and represented 10 countries. Some participants had completed high school and others had finished undergraduate or graduate studies in part or whole. Each interview was conducted online via Blue Jeans, lasting about an hour, and each transcript underwent member checking. The data were analyzed qualitatively to determine recurrent themes. Preliminary findings suggest that the predominant challenge of the participants is their lack of experience using citations before studying at the Canadian university. The participants generally had written either no formal essays or only opinion-based essays with no source requirement. In some cases, although the participants used sources, they were not required to cite them. In others, although they cited sources, they were not required to follow strict conventions like APA style. Because of the lack of citation experience, the participants found APA 7th edition rules hard to follow in the beginning. Even after the course, many participants still found paraphrase challenging because ESL students typically have limited vocabulary and grammatical structures, which make it difficult to rephrase the source in their own words while keeping the original meaning. A less serious challenge is to create a reference list of various types of sources in APA 7. To help students with the challenges, style templates and models are valuable, but perhaps even more valuable are interactive workshops at semester start offering explanations and opportunities for hands-on practice. Thus, a combination of resources and workshops along with improved language competence are expected to empower ESL students in academic integrity. By attending the session, participants will understand ESL student challenges for academic integrity and strategies to help students. Furthermore, they will receive a list of internet resources.